ANALISIS RGEC UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PADA SEKTOR PERBANKAN DI INDONESIA - Alis Safu'ah (2023)
This research is a quantitative study that aims to analyze the effect of risk profile, good corporate governance, earning, and capital as proxied by nonperforming loans, good corporate governance, return on assets, operational costs and operating income, and capital adequacy ratio to financial distress in conventional banks. 43 conventional commercial banks listed on the Indonesia Stock Exchange from 2019 to 2021 were used as samples in this study. The analysis technique used is logistic regression with the help of SPSS 26 software. Based on the statistical test results, Nagelkerke R Square is 54,8% with the conclusion that non-performing loans have an effect on financial distress in conventional banks. Meanwhile, good corporate governance, return on assets, operating costs and operating income, and capital adequacy ratios are not effect on financial distress in conventional banks.